PENGARUH “INFLUENCER” TERHADAP KEPUTUSAN PEMBELIAN DI CV. CITRA SEJAHTERA MANDIRI (ESME FASHION) - Ayu Astria; Sa'ad Noor (Ekonis: Jurnal Ekonomi dan Bisnis, 2022)
This study is intended to obtain an overview of the influence of influencer marketing on purchasing decisions at CV. Citra Sejahtera Mandiri or Esme Fashion. The research method used in this study is a quantitative descriptive method, which is a method to get an overview of the influence of influencers and purchasing decisions through questionnaire data collected from Esme Fashion customers. This study also uses the verification method by using the Spearmen rank correlation coefficient analysis technique. The results of the study indicate that there is a correlation coefficient between the influence of influencers on purchasing decisions at Esme Fashion of r = 0.844 which is classified as very strong and the Determinant Coefficient or the magnitude of the influence of influencers on purchasing decisions of 71.23%. Among the sub-variables in the influencer, the expertise Sub-Variable is the one with the highest correlation coefficient, which is 0.796, which is classified as very strong compared to the other 2 sub- variables, namely Trustworthiness of 0.758 and Attractivenes of 0.716. Based on the results of the study, the researchers concluded that there was an influencer's influence on purchasing decisions on Esme Produk. And among the Sub.Variables on influencers, the expertise Sub.Variables are Sub. Keyword: Influencer, Marketing, Purchasing